Gas Proportional Scintillation Counter with Xenon and Xenon Mixtures - Conde, C. A. N. (1968)
The light output of the recently developed gas proportional scintillation counter - a gas scintillation counter with light multiplication produced by a cylindrical geometry electric field - is investigated for heavy gaseous media under alpha particle excitation with a 56 UVP phototube. The gases used are Xe, and Xe-Ar and Xe-N2 mixtures for a wide range of concentrations, at a total pressure of about 965 Torr. The light output of the Xe-Ar mixtures shifts towards the ultraviolet (¿ ¿ 3250 Å) region as the electric field intensity increases. Xe-Ar mixtures with Xe concentrations ranging from about 1 to 10% give - with a p-quaterphenyl wavelength shifter - a light output more than two orders of magnitude larger than that of a CsI(T1) scintillator. In Xe-N2 mixtures - with wavelength shifter - nitrogen has a quenching effect. For the mixtures of noble gases the rise time of the secondary component of the light pulse is slow, typically 15 ¿s. Methane and nitrogen while having a quenching effect, reduce this rise time